Dynamic optimization approach to coordinate industrial production and cogeneration operation under electricity price fluctuations. (June 2021) - Pablos, Cristian; Merino, Alejandro; Acebes, Luis Felipe; Pitarch, José Luis; Biegler, Lorenz T.
Abstract: Industrial processes working with cogeneration utilities can coordinate their operation to take advantage of Demand Response programs to reduce their cost, while making the grid more stable and secure. Simplified steady-state and transition models are usually employed in a mathematical scheduling fashion to deal with this problem in process plants with small inertia. Here, however, we propose the use of a dynamic-integrated optimization approach that considers the dominant process dynamics jointly with the heat and power coupling in the cogeneration unit. The methodology meets the related European legislation and it has been tested in a simulated sugar factory that has a cogeneration system with connection to the external grid. The operation under two tariffs (TOU and Spanish Day-Ahead prices) was compared to the traditional policy of maximum production and fixed electricity prices, showing that a reduction of up to 5.41% of the costs is possible for the considered case study.